1989
DOI: 10.1128/jb.171.2.855-861.1989
|View full text |Cite
|
Sign up to set email alerts
|

Channel architecture in maltoporin: dominance studies with lamB mutations influencing maltodextrin binding provide evidence for independent selectivity filters in each subunit

Abstract: Maltoporin trimers constitute maltodextrin-selective channels in the outer membrane of Escherichia coli. To study the organization of the maltodextrin-binding site within trimers, dominance studies were undertaken with maltoporin variants of altered binding affinity. It has been established that amino acid substitutions at three dispersed regions of the maltoporin sequence (at residues 8, 82, and 360) resulted specifically in maltodextrin-binding defects and loss of maltodextrin channel selectivity; a substitu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
18
0

Year Published

1990
1990
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 29 publications
3
18
0
Order By: Relevance
“…In agreement with a genetic study of negative dominance and complemention between mutant LamB proteins, we find three binding sites per LamB trimer with no evidence of cooperativity between binding sites on the same trimer (11). The lack of cooperativity and the concordance of our results with those from black lipid studies reinforces the current interpretation of LamB as a simple channel with a single binding site (2,14,18,19).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In agreement with a genetic study of negative dominance and complemention between mutant LamB proteins, we find three binding sites per LamB trimer with no evidence of cooperativity between binding sites on the same trimer (11). The lack of cooperativity and the concordance of our results with those from black lipid studies reinforces the current interpretation of LamB as a simple channel with a single binding site (2,14,18,19).…”
Section: Discussionsupporting
confidence: 91%
“…This is partially based on images of negatively stained two-dimensional crystals of LamB that show three stain-filled channels merging into one (17). Genetic studies of dominance between mutant LamB proteins have suggested that each LamB monomer forms a single independent pore (11). Here, we confirm the results of this genetic study and show that maltodextrin binding to LamB can be detected in solution and the stoichiometry of binding can be measured.…”
supporting
confidence: 78%
See 1 more Smart Citation
“…Studies aimed at defining functional domains of these nonspecific porins, as well as of maltoporin LamB, have been carried out by the use of mutations in defined regions of the proteins (Heine et al, 1988;Misra & Benson, 1988a,b;Ferenci & Lee, 1989) and by the construction of hybrid proteins (Nogami, Mizuno & Mizushima, 1985;Tommassen et al, 1985;van der Ley et al, 1987, Benz et al, 1989. LamB cells grow poorly on maltose and oligosaccharides, which are presumably too bulky to enter efficiently the cell via the nonspecific OmpF and OmpC porins.…”
Section: Introductionmentioning
confidence: 99%
“…This approach is based on dimers becoming dysfunctional when one protomer is disabled. It has been used to show that lactose permease LacY functions as a monomer (30), that the small drug transporter EmrE functions as an oligomer (31), and that maltoporin functions as a trimer with three distinct selectivity filters (32,33). To establish the functional interaction between monomers, it must be possible to inactivate one protomer and to leave the second monomer unmodified and active.…”
mentioning
confidence: 99%